AUDITOR PADA LEMBAGA KEUANGAN SYARIAH - Friyanti, Yunida Een (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2017)
Abstract, Shariah audits in sharia banking is one of the most important requirement in order to maintain compliance of shariah compliance. sharia audits be well in need of good human resources also in conducting sharia audits. This research will discuss about the quality of human resources related to aspects owned by a sharia auditor. This study use theories about human resources, competence, independence. This research uses descriptive qualitative research by conducting interviews to the Sharia auditors in Yogyakarta province. The results of this study are human resources in sharia auditing in terms of competence owned by a sharia auditor there are still shortcomings and constraints, especially competence in the aspect of sharia. Related to the independence of the general shariah auditors have tried to apply independence as an auditor but still can not fully in because various aspects that can affect it such as position and reward for audit services provided.Keywords: Human Resources, Competence, Independence.